Uridine administration improves phosphatide synthesis, synaptic transmission and cognitive function - WURTMAN RICHARD J; WATKINS CAROL (2012)
The present invention provides methods of improving a cognitive function or a neurological function, treating or ameliorating a decline in a cognitive function or a neurological function, increasing cytidine levels, or treating a neurological disorder in a subject, comprising administering a uridine, a uridine precursor, or a derivative or metabolite thereof to the subject. The invention also provides methods of improving neural function, comprising contacting the neuron with a uridine, a uridine precursor, or a derivative or metabolite thereof.